Cerebrospinal Fluid Osteopontin and Inflammation-Associated Cytokines in Patients With Anti-N-Methyl-D-Aspartate Receptor Encephalitis - Zou, Cong; Pei, Shanshan; Yan, Wei; Lu, Qingbo; Zhong, Xiaomei; Chen, Qiong; Pan, Suyue; Wang, Zhanhang; Wang, Honghao; Zheng, Dong (Frontiers in Neurology, 2020)
Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is an autoimmune neurological disorder. Osteopontin (OPN) is a secreted multifunctional phosphorylated glycoprotein that regulates various autoimmune and inflammatory diseases, but its diagnostic and prognostic value in anti-NMDAR encephalitis patients remain elusive. This retrospective study aimed to determine the levels of OPN and related cytokines in cerebrospinal fluid (CSF) of anti-NMDAR encephalitis patients and to assess their influence on disease severity so as to evaluate their efficacy as biomarkers for diagnosis and prognosis. CSF samples from 33 anti-NMDAR encephalitis, 13 viral encephalitis and 21 controls were collected. All CSF were tested for levels of OPN and inflammation-associated cytokines (interleukin (IL)-6, IL-10 and tumor necrosis factor (TNF)-α) via ELISA. In addition, 15 anti-NMDAR encephalitis patients without follow-up relapse were re-examined for these four parameters 3 months later. The clinical status was evaluated by modified Rankin Scale (mRS) scores. Results showed the CSF levels of these cytokines were increased in anti-NMDAR encephalitis patients compared to controls but not viral encephalitis patients. And their levels were decreased in remission compared with that in acute stage. Moreover, CSF OPN positively correlated with IL-6, WBC counts and CRP levels in anti-NMDAR encephalitis patients. However, no associations were found between OPN or related cytokines and mRS scores in acute stage in anti-NMDAR encephalitis patients. Overall, CSF OPN and related cytokines were increased when anti-NMDAR encephalitis patients are in acute stage and decreased in remission, suggesting the underlying neuro-inflammatory process in this disease. However, they are not qualified with diagnostic or prognostic value.